Antioxidative Protective Effect of Icariin on the FeSO4/H202-damaged Human Sperm Based on Confocal Raman Micro-spectroscopy - 黄展森 肖恒军 齐涛 胡志明 李浩 陈地灵 徐亚林 陈俊 (华中科技大学学报：医学英德文版, 2014)
Oxidative stress is implicated in male infertility and significantly higher reactive oxygen species are detected in 25% of infertile males. Although different agents of various alternative medicines, including traditional Chinese medicine, have been tried with varying success, evidence remains limited on whether and how much herbs or supplements might help increase the anti-oxidant ability of the sperm. This study examined the anti-oxidative effects of icariin, a flavonoid isolated from Herba Epimedii, on the human sperm. We prepared the FeSO4/H202-damaged human sperms, which were co-cultured with icariin in vitro, and then observed the changes of the sperm by employing Raman mi- cro-spectroscopy. The results showed that Raman mapping with a 514 nm excitation laser allowed clear differentiation of the nucleus, neck, and, in particular, the mitochondria-rich middle piece of a human sperm cell. The effect oficariin on different organelles of the sperm was quantified by localized spectral Raman signatures obtained within milli-seconds, and icariin could keep the ＂Raman fingerprint＂ of the human sperm the same as the control groups, suggesting that icariin could protect the human sperm from being damaged by FeSO4/H202. Icariin may serve as a tonifying and replenishing agent of herbal origin for enhancing reproductive fimctions.